25th Anniversary Article: Ion Exchange in Colloidal Nanocrystals. (20th September 2013) - Gupta, Shuchi; Kershaw, Stephen V.; Rogach, Andrey L.
<x xml:space="preserve">Abstract</x> We review the progress in ion exchange in a variety of nanocrystal structures from the earliest accounts dating back over two decades ago to the present day. In recent years the number of groups using this method to form otherwise difficult or inaccessible nanoparticle shapes and morphologies has increased considerably and the field has experienced a resurgence of interest. Whilst most of the early work on cation exchange centered on II‐VI materials, the methodology has been expanded to cover a far broader range of semiconductor nanocrystals including low toxicity I‐III‐VI materials and the much less facile III‐V materials. The extent of exchange can be controlled leading to lightly doped nanoparticles, alloys, core‐shells, segmented rods and dots‐in‐rods. Progress has been driven by a better understanding of the underlying principles of the exchange process – from thermodynamic factors (differences in cation solubilities); the interactions between ions and transfer agents (solvents, ligands, anions, co‐dopants); ionic in‐diffusion mechanisms and kinetics. More recent availability of very detailed electron microscopy coupled with image reconstruction techniques has been a valuable tool to investigate the resulting heterostructures and internal interfaces. We start by surveying the range of synthetic approaches most often used to carry out ion exchange, mainly focusing on cation replacement strategies, and then describe the rich variety of nanostructures these techniques can bring forth. We also describe some of the principles that are used to establish the relative ease of exchange and to systematically improve the process where the basic energetics are less favorable. To help further the understanding of the underlying fundamentals we have gathered together useful data from the literature on solubilities, cation and anion hardness, ligand and solvent Lewis acid or base strengths for a wide range of chemical species generally used. We offer a perspective on the outlook for the field in terms of the emerging applications and the ion exchange derived materials that will enable them.